2020
DOI: 10.3390/en13040951
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of Excavator System Energy Flow-Down

Abstract: Due to the strengthening of air-quality regulations, researchers have been investigating methods to improve excavator energy efficiency. Many researchers primarily conducted simulation studies employing mathematical models to analyze the energy consumption of excavator systems, which is necessary to examine the fuel efficiency improvement margin and the improvement effect. However, to effectively study the improvement of excavator efficiency, the real-time energy consumption characteristics must be examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In [103] the energy flow of an excavator was analyzed in detail and it was shown that the actual energy to the final load was only the 26.6% of the hydraulic energy converted in the pump, confirming the rather low efficiency of the hydraulic system. Furthermore, in order to harness the benefits of electrification with respect to torque control, better dynamics, more accurate movements, and so on, standard hydraulic systems require the control of flow, pressure and direction, mainly by means of pressure drops, which can be regarded as intentional losses of energy [104]. Nonetheless, hydraulics is still considered essential in most off-highway vehicles and machinery due to its great power density; thus, its complete replacement is currently limited to niche products.…”
Section: Hydraulics Systems and Actuatorsmentioning
confidence: 99%
“…In [103] the energy flow of an excavator was analyzed in detail and it was shown that the actual energy to the final load was only the 26.6% of the hydraulic energy converted in the pump, confirming the rather low efficiency of the hydraulic system. Furthermore, in order to harness the benefits of electrification with respect to torque control, better dynamics, more accurate movements, and so on, standard hydraulic systems require the control of flow, pressure and direction, mainly by means of pressure drops, which can be regarded as intentional losses of energy [104]. Nonetheless, hydraulics is still considered essential in most off-highway vehicles and machinery due to its great power density; thus, its complete replacement is currently limited to niche products.…”
Section: Hydraulics Systems and Actuatorsmentioning
confidence: 99%
“…Mobile hydraulics has the highest power-to-weight ratio for actuator movement, which makes it extremely difficult to replace. At the same time, hydraulics is the biggest source of inefficiencies after the combustion engine [7], and its average energy efficiency is only as high as 21% [8]. To increase the overall efficiency of the machinery, industry and academia are researching both disruptive and incremental innovations.…”
Section: Introductionmentioning
confidence: 99%
“…In the above studies, simple signals such as constants, steps, and ramps are often used to simulate the working load, which are difficult to accurately represent the actual working condition, which will inevitably lead to deviations in the results of energy flow analysis and the effect of energy-saving schemes. In response to this problem, An et al proposed an excavator energy flow analysis method based on operating data [21], but the study did not involve the construction of typical working condition load and could not be further applied to mathematical models. Therefore, it is urgent to build up the typical working condition load of the excavator, realize the accurate analysis of the energy flow, obtain the energy margin of the excavator system, and provide accurate simulation load for the mathematical model.…”
Section: Introductionmentioning
confidence: 99%